LONTAR TUTUR KUMARA TATTWA (Kajian Singkat: Ajaran Hindu tentang Pengendalian Diri dalam Kehidupan) - I Made Suweta (Widyacarya: Jurnal Pendidikan, Agama dan Budaya, 2020)
Lontar texts that exist in Bali, mostly contain teachings imbued by Hinduism. Throwing as a legacy of ancestors is an important document that contains the concepts of ethical and moral guidance, reference to the order of life in accordance with the norms of the teachings of Hinduism. The texts of cultural heritage also contain various concepts of ancestral thought that are used as guidelines to guide behavior in society.Based on the Lontar Tutur Kumara Tattwa, several important things were obtained as a result of the study as described below. In the intrinsic study/content Lontar Tutur Kumara Tattwa discussed about: matters of life and self-control, about Lord Shiva as Istadewata, about sorga and kamoksan, and about Bhatara Siwa, Bhatara Kumara, and Liberation. In a study of Hindu teachings in the Lontar Tutur Kumara tattwa found several things: the teachings of tattwam asi, the teachings of the tri parisudha and karma phala, the teachings of Dasa Nyama Brata, and the Teachings of Dasa yama Bratha.Lontar Tutur Kumara Tattwa, needs to be further studied applicatively in other fields, both philosophically, pedagogically, and other fields. Related to this, the government; both the central and regional governments should pay special attention to the local wisdom of the Balinese region, which holds many lontar as an ancestral heritage that has a virtue value that can be used to improve human resources. Keywords: Lontar Tutur Kumara Tattwa, Intrinsic Study, Hindu Teachings